The Effects of Dietary Antioxidants on the Arginase Activity and Nitric Oxide Level of Narrow-Clawed Turkish Crayfish (Astacus leptodactylus, Esch 1823) in Moulting Period - Benzer, Fulya; Ozcelik, Mehtap; Yildirim, Nuran Cikcikoglu (Central Fisheries Research Inst, 2016)
The effects of dietary antioxidants (vitamine E, vitamine C, Astaxhantin, beta carotene) on arginase activity and nitric oxide levels of hepatopancreas and muscle of freshwater crayfish (Actacus leptodactylus) were investigated during moulting. 150 mg kg(-1) vitamine E (VE), 200 mg kg(-1) vitamine C (VC), 200 mg kg(-1) Astaxhantin and 200 mg kg(-1) beta carotene were added to experimental diets. A. leptodactylus with these diets were fed with 2% of their total weight daily, in a day during 75 days. Arginase activity was increased in muscle of crayfish fed the diets VC, VE, astaxanthin and beta karoten but in hepatopancreas arginase activity was increased with beta carotene when compared to control. NO levels in muscle were decreased when compared to control but this decrease was not statically significant. NO levels in hepatopancreas of crayfish fed the diets VC and astaxanthin were higher than control groups. Our results demonstrated that dietary antioxidants affect the arginase activity and nitric oxide level of freshwater crayfish (Astacus leptodactylus, Esch. 1823) during moulting.
Keywords: Actacus leptodactylus; Antioxidants; Arginase; Moulting Period; Nitric oxide